PEMANFAATAN LIMBAH PERTANIAN SEBAGAI ENERGI ALTERNATIF MELALUI KONVERSI THERMAL - T. Iskandar; N D. Siswati (Universitas Tribhuwana Tunggadewi, 2012)
Waste agriculture (biomassa) availability in society is quite a lot but did not yet been exploited in an optimal. Biomassa as organic matters which contain hydrocarbon compound is able as source of energi like to be is ready of heat, making fuel, and power plant. Biomassa exploiting as source of alternative energi thermal can conversion by gasifikasi process. Gasifikasi is imperfect combustion process or with limited oxygen yield CO, H2 and metan gas, used as balmy and peaceful of hot energy and also for the power of diesel, turbine etc. Besides, in course of this also yielded aqueous vapour (H2O) and dioxide carbon (CO2) which do not burnt, mote and tar. Syngas biomassa is one of product gasifikasi can be mixed with diesel fuel in room burn diesel motor moving generator to yield electric power. Mixing of diesel fuel with biomassa syngas can economize usage of diesel fuel till 70% of the amount of usage initialy, its mean that if generator set required 0,4 diesel fuel litre per kWh hence by enhancing syngas result of gasifikasi process 2 kg biomassa, required diesel fuel only 0.02 l/kWh